2.9k views
5 votes
9(k − 2) = 3(k + 4)
What’s the answer

User Nocker
by
5.0k points

1 Answer

2 votes
9(k-2)=3(k-4)

We simplify the equation to the form, which is simple to understand
9(k-2)=3(k-4)

Reorder the terms in parentheses
+(+9k-18)=3*(k-4)

Remove unnecessary parentheses
+9k-18=+3+*(+k-4+)

Reorder the terms in parentheses
+9k-18=+(+3k-12)

Remove unnecessary parentheses
+9k-18=+3k-12

We move all terms containing k to the left and all other terms to the right.
+9k-3k=-12+18

We simplify left and right side of the equation.
+6k=+6

We divide both sides of the equation by 6 to get k.
k=1

User Hixi
by
5.0k points